Ross Silcock letter to Thomas Kent regarding spring notes, June 5, 1981 - Silcock, W. Rosset al (1981)
The letter includes a list of birds sighted by Ross Silcock. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed